Lexical Relations in Joe Biden's Speech about Plan to Lower Prescription Drugs Cost: Semantics Study - Sefina Putri Miharsa; Heri Heryono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to analyze the types of lexical relations and the types of meanings of lexical relations that appear in Joe Biden's Speech about the plan to reduce prescription drug prices. The method used in this research is qualitative method. The results of this research show that there are eight types of lexical relations and three types of semantic meanings; the types of lexical relations show that from 30 data that have been analyzed, eight synonym data (26.7%), ten antonym data (33.3%), three meronym data (10%), two polysemy data (6.7%), two hyponym data (6.7%), two member-collection data (6.7%), two portion-mass data (6.7%), and one homonym data (3.3%). Meanwhile, the types of semantic meanings found from 60 data that have been analyzed are 51 data of literal meaning (85%), 5 data of semi-idiomatic meaning (8.3%), and 4 data of fully idiomatic meaning (6.7%). Therefore, it can be concluded that the type of lexical relations that appears the most is antonyms at 33.3% and that the most common type of meaning is literal meaning, which is 85%. Keywords: Lexical relations, Semantics, Speech